Como subir nas tranças que a bruxa cortou? Produção textual de alunos com e Síndrome de Down - Gomes, Adriana Leite Limaverde (2006)
This study it considers an analysis of the written productions of students with and without Down syndrome. Its main objective is to understand its limits and possibilities in materializing and organizing its texts. In order to analyze the writing of these students, we collect five texts - the rewrite of the story of Rapunzel, the writing with images with and without the use of the mediation, the rewrite of the history of the Totó dog, with the request of change of the outcome and the production of a ticket of twenty one students of different schools of the city of Fortaleza - CE. The collection made in the period of two years, in four distinct phases, it characterizes a qualitative research of the comparative type. The passage of this inquiry understands four main phases: 1ª) exploratória phase; 2ª) study pilot; 3ª) sessions of evaluation with eleven pupils with Down syndrome and 4ª) sessions of evaluation with ten students without Down syndrome. Our analysis disclosed qualitative similarities between the two groups, in relation to the appropriation of the ortografic norm and to the use of the punctuation signals. We evidence the concentration of errors for omission and exchanges of letters. In the use of the punctuation, the participants had centered the job of the end point to delimit the closing of the text. A job of the punctuation nor always occurred of adequate form. We verify significant differences between the two groups in the linguistic-literal aspects. Some productions of the students with Down syndrome had expressed a writing without the presence of characteristic elements of the written language. In a general way, these productions are included by the writing of untied and broken up words, with the predominance of the register of substantives and verbs. While, the said students normal had presented greater coherence in the job of the words and the felt construction of the text. Nor always, however, the pertaining to school advance determined the best quality in the literal productions. Finally, we conclude that, throughout the development of the writing, the practical pertaining to school and the experiences diversified with the reading and the writing influence in the written production, independently of the cognitive condition of the student.